Producer of controversy : Stanley Kramer, Hollywood liberalism and the Cold War - Frost, Jennifer (University Press of Kansas, 2017)
Through his career, politics, and films, Hollywood filmmaker Stanley Kramer significantly shaped American culture during the Cold War.
Keywords: Kramer, Stanley -- Criticism and interpretation.; Kramer, Stanley; Politics in motion pictures.; Politique au cinéma.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Politics in motion pictures; Electronic books.; Criticism, interpretation, etc.